Asymmetric aza-Henry reaction toward trifluoromethyl β-nitroamines and biological investigation of their adamantane-type derivatives - Ren, Yi; Du, Mengyuan; Peng, Ziyu; Zheng, Changwu; Zhao, Gang (Frontiers in Chemistry, 2024)
Amino acid-derived quaternary ammonium salts were successfully applied in the asymmetric aza-Henry reaction of nitromethane to N-Boc trifluoromethyl ketimines. α-Trifluoromethyl β-nitroamines were synthesized in good to excellent yields with moderate to good enantioselectivities. This reaction is distinguished by its mild conditions, low catalyst loading (1 mol%), and catalytic base. It also proceeded on a gram scale without loss of enantioselectivity. The products were transformed to a series of adamantane-type compounds containing chiral trifluoromethylamine fragments. The potent anticancer activities of these compounds against liver cancer HepG2 and melanoma B16F10 were evaluated. Six promising compounds with notable efficacy have potential for further development.